2010
DOI: 10.1093/ije/dyq102
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol increases circulatory disease mortality in Russia: acute and chronic effects or misattribution of cause?

Abstract: Background There is a consensus that the large fluctuations in mortality seen in Russia in the past two decades can be attributed to trends in alcohol consumption. However, the precise mechanisms linking alcohol to mortality from circulatory disease remain unclear. It has recently been argued that a substantial number of such deaths currently ascribed to cardiovascular disorders are misclassified cases of acute alcohol poisoning.Methods Analysis of routine mortality data and of a case–control study of mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 31 publications
3
55
0
8
Order By: Relevance
“…Similar misclassifications were found in other regions of Russia and surrounding countries 49. However, while this means that alcohol poisoning deaths have been under‐reported, this effect is too small to explain the positive association between heavy drinking and cardiovascular mortality in countries with irregular drinking of very large amounts of alcohol, such as the eastern European countries 50, 51. The second reason for the underestimation of alcohol poisoning are the rules applied to classify drug overdose deaths in ICD‐10 or earlier versions of the ICD 52, which give a priority for coding other substances than alcohol in case of involvement of multiple types of substance use in deaths (see also 53, 54).…”
Section: Resultsmentioning
confidence: 60%
“…Similar misclassifications were found in other regions of Russia and surrounding countries 49. However, while this means that alcohol poisoning deaths have been under‐reported, this effect is too small to explain the positive association between heavy drinking and cardiovascular mortality in countries with irregular drinking of very large amounts of alcohol, such as the eastern European countries 50, 51. The second reason for the underestimation of alcohol poisoning are the rules applied to classify drug overdose deaths in ICD‐10 or earlier versions of the ICD 52, which give a priority for coding other substances than alcohol in case of involvement of multiple types of substance use in deaths (see also 53, 54).…”
Section: Resultsmentioning
confidence: 60%
“…To the authors' knowledge, no studies have investigated the relationship between risk perception and alcohol consumption. Conversely, many studies have found that alcohol consumption clearly affects the risk of CVD (Leon, Shkolnikov, McKee, Kiryanov, & Andreev, 2010). Thus, an increase in perceived risk accompanying increased alcohol use may reflect an appropriate awareness of this risk of CVD.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, an increase in perceived risk accompanying increased alcohol use may reflect an appropriate awareness of this risk of CVD. The precise mechanism linking alcohol to the risk of CVD, however, remains unclear (Leon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the substantial decline in acute alcohol poisoning in 2004-2010 was, unusually, accompanied by a persistently high rate of mortality from liver cirrhosis. While we cannot exclude some change in coding practices, this may indicate a reduction in the frequency of the kind of extreme drinking behavior associated with alcohol poisoning, even as the overall level of alcohol consumption remains high, which may be expected to result in chronic damage affecting not only the liver, but also the pancreas, heart, and other organs (Leon et al 2010).…”
Section: Alcoholmentioning
confidence: 99%